2020
DOI: 10.18343/jipi.25.2.284
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Electro-Coagulation Technique in Reducing Organic Materials in Waste Water of Fish Culture

Abstract: Elektrokoagulasi merupakan salah satu teknik pengolahan secara fisik yang dapat diterapkan untuk mengolah air limbah pemeliharaan ikan. Penelitian eksperimental ini bertujuan untuk menentukan besar tegangan listrik dan waktu yang efektif teknik elektrokoagulasi dalam pengolahan air limbah. Beberapa perlakuan perbedaan besar (6 dan 12V) selama 15, 30, 45, dan 60 menit diterapkan dalam pengujian. Hasil eksperimen menunjukkan adanya perubahan, berupa peningkatan maupun penurunan kualitas air, dari kondisi awal ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Electrocoagulation contact time can increase th e efficiency of pollutant removal [49,65]. Lastly, the 60-minute contact time of electrocoagulation with aluminum electrodes was found to be the most effective in increasing the pH value [66][67][68].…”
Section: Resultsmentioning
confidence: 99%
“…Electrocoagulation contact time can increase th e efficiency of pollutant removal [49,65]. Lastly, the 60-minute contact time of electrocoagulation with aluminum electrodes was found to be the most effective in increasing the pH value [66][67][68].…”
Section: Resultsmentioning
confidence: 99%
“…Based on the research conducted by Fitri et al (2020) found that the percentage level of removal of COD and TSS levels in the of fishery activities using the electrocoagulation method that is equal to 82.89% and 31.90% which occurs at a voltage of 12 volts within 60 minutes and 15 minutes (Radityani et al, 2020). Then the research conducted by Ni'am et al (2017) showed that the optimum conditions for removal of COD and TSS levels in textile wastewater were obtained at a voltage of 12 volts within 45 minutes with a percentage level of removal of COD and TSS levels of 76% and TSS of 85%.…”
Section: Introductionmentioning
confidence: 99%